Edukasi Dan Implementasi Supply Chain Management Untuk Optimalisasi Stok Di Vending Machine: Education and Implementation of Supply Chain Management for Stock Optimization in Vending Machines - Rommy, Lambok (BALQIS : Journal of Business Innovation and Digital Marketing, 2025)
Vending machine management requires a structured inventory management system to ensure product availability and minimize operational costs. This study discusses the implementation and education of Supply Chain Management (SCM) in an effort to improve efficiency, refill effectiveness, and inventory optimization in vending machines. Based on discussions in the literature and analysis of SCM concepts in the file, it was found that information flow plays an important role in ensuring that replenishment decisions are made on time and in the right quantities. SCM education helps operators understand the importance of demand forecasting, determining minimum-maximum inventory levels, and using sales data to predict the needs of each machine. The results of the discussion show that the application of SCM can reduce stockouts and stockpiling through data-based refilling, rather than habit. Effectiveness is increased because the product composition can be adjusted to the characteristics of the location, so that goods rotation becomes faster. In terms of efficiency, the frequency of refilling trips can be reduced through more optimal distribution route planning. Additionally, better coordination with suppliers enhances supply reliability and reduces the risk of delays. In conclusion, SCM education and implementation have a significant impact on improving vending machine management performance. With more accurate inventory control, more scheduled restocking, and more efficient distribution, the application of SCM has been proven to increase profitability, reduce operational costs, and strengthen the overall sustainability of the vending machine system.